Genicular Nerve Ultrasound-Guided Cryoanalgesia for the Treatment of Chronic Knee Joint Pain: An Observational Retrospective Study - Giuliano Lo Bianco; Francesco Paolo D’angelo; Guillherme Ferreira Dos Santos; Agnes Stogicza; Matteo Luigi Giuseppe Leoni; Andrea M. Trescot; Robert Jason Yong; Christopher L. Robinson (Pain and Therapy)
Abstract Introduction Chronic knee pain caused by osteoarthritis (OA) is a prevalent source of disability in the adult population. Total knee arthroplasty (TKA) is an effective surgical treatment for advanced disease, but many patients continue to suffer from chronic post-surgical pain (CPSP). In recent years, minimally invasive techniques targeting peripheral nerves have been explored. Cryoanalgesia of the genicular nerves (GNCryo) is one such intervention that disrupts sensory input by applying extremely low temperatures to the target nerves, potentially leading to sustained pain relief without the need for neurodestructive heat lesions. This study aims to evaluate the effectiveness of ultrasound-guided GNCryo in patients with chronic knee pain due to primary OA or CPSP after TKA. Methods This retrospective, single-center study included 90 patients who underwent GNCryo between September 2021 and February 2023. Inclusion criteria were patients over 18 years of age, symptomatic knee OA or CPSP after TKA, and a positive response (≥ 50% pain relief) to diagnostic genicular nerve blocks. Ultrasound guidance was used to optimize needle placement and reduce complications. Clinical outcomes were assessed at baseline and at 1, 3, 6, and 9 months post-procedure. Outcome measures included the Visual Analog Scale (VAS, 0–10) for pain intensity, the Western Ontario and McMaster Universities Arthritis Index (WOMAC, 0–100) for assessing pain, stiffness, and physical function related to OA, the Douleur Neuropathique en 4 Questions (DN4, 0–10) for neuropathic pain, and the EuroQol 5-Dimension (EQ-5D, 0–100) for quality of life. Results Ninety patients completed the 9 months follow-up. The median VAS score decreased from 7.0 (6.0, 8.0) at baseline to 4.0 (3.0, 5.0) at 1 month, remained at 4.0 (3.0, 5.0) at 3 months, and increased slightly to 5.0 (4.0, 5.0) at 6 months and 5.0 (4.0, 6.0) at 9 months, yet pain relief remained lower than baseline. WOMAC scores decreased from 65 (55, 71) at baseline to 35 (30, 40) at 1 month and 35 (30, 40) at 3 months, increased to 40 (35, 50) at 6 months and 55 (45, 65) at 9 months. DN4 scores decreased from 7 (5, 8) at baseline to 4 (3, 4) at 1 month and 3 (2, 4) at 3 months, increased to 3.5 (3, 5) at 6 months and 5 (4, 6) at 9 months, yet remained lower than baseline. EQ-5D scores increased from 64.5 (47, 84) at baseline to 42 (32, 58) at 1 month, 43.5 (31, 59) at 3 months, 45.5 (35, 60) at 6 months, and 52 (41, 72) at 9 months. Conclusions Ultrasound-guided GNCryo is a promising minimally invasive treatment for chronic knee pain, providing pain relief and improved quality of life for up to 9 months. Although some outcomes showed a trend toward baseline over time, pain relief remained lower than baseline, consistent with potential nerve regeneration or recovery. Larger prospective, controlled trials are necessary to confirm these findings and to refine patient selection and technique optimization.